BRCA1 Positivity in Triple Negative Breast Cancers: A Prospective Study in Tertiary Care Cancer Hospital - Manisha Sharma; Manas Madan; Mridu Manjari; Mohit Madhukar; Taranveer Singh; Shruti Gupta (Tropical Journal of Pathology and Microbiology, 1970)
Objectives: In the present study we investigated the BRCA1, Estrogen receptors status (ER), progesterone receptor status (PR) and human epidermal growth factor receptor (Her2neu) expression in selected patients with higher probability of BRCA1 positivity. The association of BRCA1 positivity and Triple Negative Breast Cancer (TNBC) status was also demonstrated.Materials and Methods: The study was conducted on 100 cases of breast cancer specimen received in department of Pathology, SGRDIMSAR, Amritsar. Histopathological typing and grading was done followed by immunohistochemistry for BRCA1, ER, PR and Her2neu.Results: All the tumors were infiltrating ductal carcinoma NOS. 4 cases were of grade I, 34 cases as grade II and 62 as grade III. ER+ PR+ Her2neu-ve cases comprised of 33% and triple negative being 38%. BRCA1 positivity was seen in 36% patients. BRCA1 positivity was significantly higher in triple negative primary tumours as compared to other groups. (23/38- 60.5% vs 13/62-20.9% respectively) with significant p =0.009.Conclusion: Triple Negative Breast Cancer (TNBC) patients are associated with poor prognostic factors and are more likely to be BRCA1 positive. Such BRCA1 identification is not only important in management of the patient for contralateral breast cancer and ovarian cancer but also blood relatives of such patients. As the relatives of such patient have 50% of increased chances of BRCA1 expression.